On Putting an End to the Backlash Against Electrophysical Agents - Alain-Yvan Belanger; David M. Selkowitz; Daryl Lawson (International Journal of Sports Physical Therapy)
Electrophysical agents (EPAs) are core therapeutic interventions in academic physical therapy curricula around the world. They are used concomitantly with several other therapeutic interventions such as exercise, manual therapy techniques, medications, and surgery for the management of a wide variety of soft tissue disorders. Over the past decade, the practice of EPAs has been the subject of intense scrutiny in the U.S. This has been colored by some physical therapists publicly engaging in bashing rhetoric that has yet to be officially and publicly addressed by the guiding organizations which, together, regulate the practice of physical therapy in this country. Published in world renowned public media are unsubstantiated mocking remarks against the practice of EPAs and unethical allegations against its stakeholders. This rhetoric suggests that EPA interventions are "magical" treatments and that those practitioners who include them in their plans of care may be committing fraud. Such bashing rhetoric is in striking contradiction to the APTA's Guide to Physical Therapist Practice 4.0, which lists EPAs as one of its categories of interventions, the CAPTE's program accreditation policy, and the FSBPT's national licensing exam. The purpose of this commentary is to expose the extent of this discourse and to call to action the APTA, CAPTE, and FSBPT organizations, as well as physical therapists, with the aim at putting an end to this rhetoric.